Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Melalui Motivasi Kerja Sebagai Variabel Intervening Pada UD Eko Plastik - Noviandhi Sanggar Nirvandhi; Eny Setyariningsih; Toto Heru Dwihandoko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
In this era, all companies are competing to develop their respective businesses so they can compete. The most effective way of developing a business is by maximizing the management of existing resources, and the resource that has the most important role, namely human resources. Companies can maximize the management of their human resources so that they can produce a maximum performance. There are several things that can affect performance, namely the work environment, work discipline and work motivation. The purpose of this research is to determine the effect of the work environment and work discipline on employee performance with work motivation as an intervening variable at UD. Eko Plastik. This research was conducted by distributing questionnaires to UD. Eko Plastik employees. The population in this study are all employees of UD. Eko Plastik. The sample of this research was 250 people using saturated sample technique. The data analysis technique uses SEMPLS with the help of the SmartPLS program. The results of this reseacrh are that the work environment has a direct positive and significant effect on work motivation, work discipline has a direct positive and significant effect on work motivation, the work environment has a direct positive and significant effect on employee performance, work discipline has a direct positive and significant effect on employee performance, work motivation has a direct positive and significant effect on employee performance, the work environment has a positive and significant indirect effect on employee performance through work motivation, work discipline has an indirect positive and significant effect on employee performance through work motivation.